Humanitarian Crisis and Failure of International Community: A Study of Plight of Rohingya Muslims in Myanmar - Syed Mohammad Raghib; Kamran Naseem (ASIAN Journal of International Peace & Security (AJIPS), 2023)
The Rohingya refugee crisis is one of the world’s most terrible incidents, which has been reported since 2012. Rakhine State Riot’s images shared on social media sparked in a big manner globally. Since 2016, government forces have brutally killed thousands of people. Organized mobs and army units have brutally handled and killed people. However, this paper critically looks for insights into Rohingya’s historical and ethnic linkage. The paper also looks at Myanmar’s regressive approach towards Rohingya and the state’s actions. The paper used descriptive methodology, and regressive state behaviour and analyzed the prosecution of Rohingya people through the human rights approach. This paper analyzes how a world-renowned human rights face, Aun San Suu Kyi, a winner of the Noble Peace Prize in 1991, neglected the issue of human rights. The other aspect of the paper highlights neighbour countries like India and Bangladesh, where these Rohingya refugees settled down under the UNHCR. The question is, why did the UN and World powers have not taken action against the brutal regime promptly? Why the world left them to suffer for so long, despite international human rights agencies and neighbours even the Muslim and Islamic World’s effective presence?